Dual Training in Teacher's Degrees: Interactive Feedback in the Competences Assessment - M. Inés Gabari Gambarte; Jaione Apalategi Begiristain (Universidad Autónoma de Madrid, 2019)
The evaluation by competences in the space of higher education that introduced the so-called Bologna process continues to be a challenge faced by the university institution for two decades. The proposal of good practices in the Initial Training of the Degrees of Master, collected in this article, aims to implement a dual university-primary school training process as a scenario for the development and evaluation of the specific competences of the subject Processes and Educational Contexts/Hezkuntza Prozesuak eta Testuinguruak offered in the second school year of the curriculum in various languages (Spanish and Basque -official languages- and English) at the Public University of Navarra/Nafarroako Unibertsitate Publikoa. We opt for an associative exterior design that has been consolidated in the last six years and in which 400 university students have participated. The results describe the logical sequence of the stages, means, techniques and evaluation instruments, as well as the participation of the different agents involved in the self-regulation of competency learning, so that it is an authentic, participatory and shared evaluation. The conclusions point to the importance of creating spaces of alternation that connect university learning with contextualized practice, so that they respond to social demands and that, in turn, entail the proper accreditation of the levels of competence acquired.